Briquette from Candlenut Shell Charcoal and Polypropylene Plastic Waste From The Kefamenanu Landfill - Giovanny Robertho Wolfram Lake; Gebhardus D Gelyaman; Sefrinus M.D. Kolo (Jurnal Sains dan Terapan Kimia, 2023)
This research aimed to determine the optimum composition of polypropylene plastic and candlenut shell charcoal in briquettes production. The percentage of briquette mixture was CK100:0PP, CK75:25PP, CK50:50PP, CK25:75PP and CK0:100PP. The moisture content of the briquettes obtained was as follows CK100:0PP (6.33%), CK75:25PP (4.18%), CK50:50PP (2.63%), CK25:75PP (1.90%) and CK0: 100PP (0.77%). Ash content was CK100:0PP (0.51%), CK75:25PP (18.82%), CK50:50PP (9.09%), CK25:75PP (3.26%) and CK0:100PP (1.74%). The level of flying substances was CK100:0PP (33.53%), CK75:25PP (51.52%), CK50:50PP (52.37%), CK25:75PP (60.99%) and CK0:100PP (72.96%). Fixed carbon was CK100:0PP (59.63%), CK75:25PP (25.48%), CK50:50PP (35.91%), CK25:75PP (33.85%) and CK0:100PP (24.52 %). Calorific value was CK100:0PP (2,902.31 cal/gr), CK75:25PP (9,292.45 cal/gr), CK50:50PP (8,155.53 cal/gr), CK25:75PP (9,094.69 cal/gr) and CK0:100PP (10,808.30 cal/gr). Compressive strength was CK75:25PP (50.31 Kgf/cm2), CK50:50PP (44.67 Kgf/cm2), CK25:75PP (36.11 Kgf/cm2) and CK0:100PP (33.85 Kgf/cm2). The optimum composition of briquettes from a mixture of polypropylene plastic and candlenut shell charcoal was CK25:75PP.